Decentralisation, quality of government and economic growth in the regions of the EU - Rune Dahl Fitjar; Jonathan Muringani; Andrés Rodríguez-Pose (Revista de Economía Mundial, 2019)
The effect of decentralisation on regional economic growth is a hotly debated topic. In theory, decentralisation should entail welfare benefits by bringing government closer to the people. In practice, the benefits of decentralisation have been hard to prove. A problem is that the quality of regional governments is often lacking, or at least varies widely across different regions. Hence, regional governments may not be capable of delivering public goods in an efficient and accountable manner. However, previous analyses have neglected how the benefits of decentralisation may depend on the quality of the regional government whose authority is strengthened by such reforms. This paper considers these two dimensions in conjunction, highlighting that the effect of decentralisation on economic performance is highly mediated by the quality of the devolved government. Using panel data for 223 regions in the EU, the results show that the quality of regional government is a better predictor of economic development than decentralisation. Regional government quality also conditions the economic returns to decentralisation, meaning decentralisation works best in regions with a higher quality of government. Accordingly, decentralisation reforms must consider the quality of the regional government to which they would devolve authority.